EFFECT OF WORK ENVIRONMENT ON EMPLOYEE SATISFACTION WITH WORK COMMUNICATION AS INTERVENING VARIABLE - Rumiris Siahaan (Bajang Institute, 2022)
This research shows. (1) It can be seen that the adjusted R square value is 0.586 or 58.6%. This shows that work communication (Z) and work environment (X) can explain job satisfaction (Y) by 58.6%, the remaining 41.4% (100% - 58.6%) is explained by other variables outside the model. this research. (2) The results of the t-test (partial) can be seen that the obtained tcount (7.526) > ttable (2.028), as well as the significance value of 0.00 <0.05, it can be concluded that the first hypothesis is accepted, meaning that the work environment variable (X) positive and significant effect on work communication (Z). (3) The results of the t-test (partial) can be seen that the value of tcount (3.034) > ttable (2.028), and the significance value of 0.005 <0.05, it can be concluded that the second hypothesis is accepted, meaning that the work environment (X) has a significant effect on job satisfaction. (Y). (4) The results of the path analysis test show that the direct effect of variable X on variable Y is 0.515. Meanwhile, the indirect effect through the Z variable is 0.782 x 0.309 = 0.241. From the calculation results obtained, the indirect effect through the Z variable is greater than the direct effect on the Y variable.